The influence of bacterial vaginosis on gestational week of the completion of delivery and biochemical markers of inflammation in the serum - Jakovljević, Ana; Bogavac, Mirjana; Nikolić, Aleksandra; Milošević Tošić, Mirjana; Novaković, Zoran; Stajić, Zoran (Vojnosanitetski pregled, 2014)
Bacground/Aim. Preterm delivery is one of the most common complications in pregnancy, and it is the major cause (75–80%) of all neonatal deaths. Bacterial vaginosis predisposes to an increased risk of preterm delivery, premature rupture of membrane and miscarriage. In this syndrome normal vaginal lactobacilli, which produce protective H2O2, are reduced and replaced with anaerobic, gram-negative bacteria and others. The aim of this study was to evaluate the influence of bacterial vaginosis on the week of delivery and biochemical markers of inflammation in the serum. Methods. A total of 186 pregnant women were included into this study, between the week 16 and 19 of pregnancy. In the study group there were 76 pregnant women with diagnosed bacterial vaginosis by the criteria based on vaginal Gram-stain Nugent score and Amsel criteria. In the control group there were 110 healthy women with normal vaginal flora. Ultrasound examination was performed in both groups. Vaginal fluid and blood samples were taken to determine biochemical markers with colorimetric methods. Results. The week of delivery was statistically significantly shorter in the study group and the levels of biochemical markers of inflammation (C-reactive protein and fibrinogen in the serum) were statistically significantly higher in women with bacterial vaginosis comparing to the control group. Also the levels of uric acid and white blood cells in the serum were higher in the study group compared to the control one. Conclusion. Our study indicates that the pregnancy complicated with bacterial vaginosis ends much earlier than the pregnancy without it. Also, higher levels of biochemical markers of inflammation in the serum in the study group, similarly to results of other studies, suggest that pathophysiological processes responsible for preterm delivery can begin very early in pregnancy.